2021
DOI: 10.1108/jfra-11-2020-0321
|View full text |Cite
|
Sign up to set email alerts
|

Value relevance of earnings and book values during IFRS convergence period in India

Abstract: Purpose The authors aim to examine the association between earnings and book values with stock prices in India during the IFRS convergence period because, in India, the literature is yet to investigate more about IFRS convergence and its impact on the financial reporting environment. Hence, the purpose of this study is to assess the influence of IFRS conversion on the value relevance of accounting information throughout the IFRS conversion period. Design/methodology/approach The current paper endeavors to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 75 publications
2
18
0
Order By: Relevance
“…Chen et al (2001) have reported that book value and earnings are value-relevant in various segments of the Chinese stock market based on empirical evidence from 1991 to 1998. Other researchers (Ragab and Omran, 2006;Bae and Jeong, 2007;Pourheydari, Aflatooni, and Nikbakhat, 2008;Al-Hares, AbuGhazaleh, and Haddad, 2012;Bilgic and _ Ibis, 2013;Omokhudu and Ibadin, 2015;Ahmadi and Bouri, 2018;Rahman and Liu, 2021;Srivastava and Muharam, 2021;Cupic et al, 2022) have found similar results in different global markets. Ragab and Omran (2006) have conducted research to examine the relevance of earnings value and book value in the Egyptian Stock Market from 1998 to 2002.…”
Section: Review Of Literature and Development Of Hypothesesmentioning
confidence: 72%
“…Chen et al (2001) have reported that book value and earnings are value-relevant in various segments of the Chinese stock market based on empirical evidence from 1991 to 1998. Other researchers (Ragab and Omran, 2006;Bae and Jeong, 2007;Pourheydari, Aflatooni, and Nikbakhat, 2008;Al-Hares, AbuGhazaleh, and Haddad, 2012;Bilgic and _ Ibis, 2013;Omokhudu and Ibadin, 2015;Ahmadi and Bouri, 2018;Rahman and Liu, 2021;Srivastava and Muharam, 2021;Cupic et al, 2022) have found similar results in different global markets. Ragab and Omran (2006) have conducted research to examine the relevance of earnings value and book value in the Egyptian Stock Market from 1998 to 2002.…”
Section: Review Of Literature and Development Of Hypothesesmentioning
confidence: 72%
“…A study on the explanatory power of accounting variables on the market prices of shares in Germany and the UK by Elbakry et al (2017) suggested long-run Grangercausality of the accounting variables on the share prices in the UK, unlike the German markets due to the evolution of the standards in a highly politicized environment in the country. The earnings and book value has value relevance during the IFRS enforcement period in the Indian market, with a slight weakness in the book value compared to the earnings with the share price (Srivastava & Muharam, 2021). The findings of the study on the value relevance of book values and earnings in Indonesia and India revealed that it increased during the period when IFRS was enforced.…”
Section: Literature Reviewmentioning
confidence: 90%
“…The findings of the study are, however, based on the analysis of only two years, as it compares one year each as a pre-and post-IFRS year. Similarly, Srivastava and Muharam (2021) carry out a cross-sectional and pooled data analysis on Indian financial reporting data between 2015-2019. They observe a gradual increase in the year-wise adjusted R 2 , implying an increase in value relevance.…”
Section: Impact Of Ifrs Implementation On the Value Relevance Of Acco...mentioning
confidence: 99%
“…Value relevance studies of Indian firms have revealed a positive relationship between accounting information and market values (Bhatia & Mulenga, 2019;Robu et al, 2017;Sharma et al, 2012;Vardia et al, 2016). However, few researchers have addressed the issue of value relevance since the IFRS convergence process began in India using relatively smaller samples (Bansal & Garg, 2021;Kaur & Yadav, 2020;Srivastava & Muharam, 2021;Vardia et al, 2016). The aim of this paper is, therefore to widen the knowledge on Indian financial reporting quality in the post-IFRS convergence phase using returns value relevance as the quality metric.…”
Section: Introductionmentioning
confidence: 99%